Analisis Advertorial DPRD Bandung di Pikiran Rakyat, Tribun Jabar, Koran Gala dan Radar Bandung - Pitoyo; Ramadhani, Rizky Wulan (Kinesik, 2026)
This study aims to analyze advertorials in the era of digital media and AI. The findings serve as recommendation material for the Bandung City DPRD in budgeting for print media advertorials. This study employs SWOT Analysis, pioneered by Albert Humphrey in the 1960s, an acronym for Strengths, Weaknesses, Opportunities, and Threats. This analysis is a strategic planning tool used to evaluate the internal and external factors of an advertorial. The advertorials studied are from the print media Pikiran Rakyat, Tribun Jabar, Koran Gala, and Radar Bandung. The method involves gathering media data and collecting secondary data from accredited international and national journals as the basis for analysis. The study's results indicate that print media advertorials remain effective in conveying news messages and even serve as public references. The reason is that advertorials are narrative messages with a gatekeeper (content guardian), making them free from the spread of hoaxes or fake news.